Federalization of Agriculture Sector: Issues and Challenges - Bishwakarma, Bishnu Kumar (Nepal Public Policy Review, 2022)
The research examines the current issues and challenges of sectoral restructuring and assesses local governments' performance in agricultural service delivery at the local level under the federal system in Nepal. This study was conducted using a mixed method during 2019-2021 in three local governments at the local, Karnali Province, and federal levels. Qualitative methods such as KIIs, FGDs and field observations were used to analyze the issues and gaps in functions, institutions and policies in the agriculture sector under the federal system. Whilst qualitative methods and an empirical survey among 300 farming households were conducted to assess local governments' performance in agricultural service provisions. The qualitative data were analyzed using the thematic analysis method, and the quantitative data were analyzed using descriptive statistics such as frequency and percentage. Findings revealed that functional overlap, duplication and lack of coordination between the three tiers of the government as major issues in sectoral restructuring. Farming household surveys revealed that local governments are effective in the timely delivery of agricultural services. However, farmers indicated their lower level of agreement on the capacity of the local staff, policies, institutional mechanisms, participatory process in planning and financial resource allocation for agricultural services. The performance of these three local governments on agricultural service delivery was affected by leadership priority and commitment, local policies, local staff capacity, resource allocation and external support. Overlapping and duplication in service delivery roles, weak local capacity, higher conditionality of intergovernmental sectoral fiscal transfer and less priority of local governments in financial resource prioritization are current issues and gaps in agricultural service delivery. The findings suggest the demarcation of the roles and responsibilities between the three tiers of the government, strengthening local capacities and revisiting local governments' institutional arrangement for effective agricultural service delivery under the federal system.